Using the ELMERI Observation Method to Investigate and Compare Laboratories at Isfahan Public Health School in Terms of Occupational Health and Safety - Ehsanollah Habibi; Sayed Mahdi Mousavi; Hossein Ebrahimi; Mojtaba Nakhaei pour (International Journal of Environmental Health Engineering)
Aims: The present study aims to investigate laboratory safety situations using the ELMERI observation method. Methods: This cross-sectional study was conducted in 2023 in the Faculty of Health, Isfahan University of Medical Sciences laboratory. The survey data were applied with the ELMERI observation method, and the laboratories’ safety indicators were evaluated. Results: The findings provide important insights into the current state of laboratory safety. The average ELMERI index score for the laboratories was 69.32, indicating that overall health and safety performance is at an average level. Laboratories in five dimensions of building safety, safety of devices and equipment, personal safety, safety of chemicals, and waste management were at a good level. However, in three dimensions of electrical safety, fire safety, and safety management and the dimension of emergency response management, there is room for improvement. Conclusion: The general safety situation in the laboratories is at an average level, highlighting the need for better planning at the university and faculty levels. Enhanced planning is essential for improving safety management, particularly in emergency response and can have a significant impact on occupational health and safety in laboratories.